Mesothelin expression remodeled the immune-matrix tumor microenvironment predicting the risk of death in patients with malignant pleural mesothelioma - Qualiotto, Aline Nery; Baldavira, Camila Machado; Balancin, Marcelo; Ab’Saber, Alexandre; Takagaki, Teresa; Capelozzi, Vera Luiza (Frontiers in Immunology, 2023)
Background The combination of immunobiological agents with immune checkpoint proteins is a promising treatment for malignant pleural mesothelioma (MPM). Mesothelin and anti-PD-L1 antibody-drug conjugates specifically target malignant neoplastic cells, inhibit the migration and invasion of neoplastic cells, and restore the immune landscape. In this study, we confirmed the importance of mesothelin and examined the relationship between mesothelin and the immune landscape of the tumor microenvironment (TME) in two MPM cohorts. Methods The discovery cohort included 82 MPM cases. Tissue microarray slides were generated, and samples were processed for hematoxylin & eosin staining, immunohistochemistry, and immunofluorescence assays. The relationship between mesothelin, biomarkers of histogenesis, histological aggressiveness, PD-L1, immune cells (CD4, CD8, CD20, CD68), and collagen type I and type V fibers was evaluated by quantitative digital analyses. The outcome was the survival time until death from disease recurrence. The exploratory cohort included 87 malignant mesothelioma (MESO) patients from The Cancer Genome Atlas database. Results Most patients were male (70.7%) with a history of asbestos exposure (53.7%) and with the epithelioid subtype (89%). Surgical resection was performed in 85.4% of patients, and 14.6% received chemotherapy; 59.8% of patients died from disease extension to the mediastinum. Low tumor mesothelin expression was associated with tumor necrosis and nuclear grade 1, whereas high mesothelin expression was significantly associated with the epithelioid histotype and high density of T cells CD8+, macrophages CD68+, and collagen type I fibers. Cox multivariate analysis showed a high risk of death for non-operated patients [hazard ratio (HR), 3.42 (1.15–10.16)] with low tumor mesothelin levels [HR, 2.58 (1.09–6.10)] and high PD-L1 and low infiltration of T cells CD4+ [HR, 3.81 (1.58–9.18)]. In the exploratory cohort, low mesothelin and high COL1A1 and COL5A1 expression were associated with poor overall survival. Conclusion Tumor mesothelin expression associated with the TME immune landscape predicts the risk of death for patients with MPM and could be a new target for immunotherapy in MPM.